Duke Ellington the piano prince and his orchestra - Pinkney, Andrea Davis (Jump at the Sun/Hyperion Paperbacks for Children, 2007)
A brief recounting of the career of this jazz musician and composer who, along with his orchestra, created music that was beyond category.